2020
DOI: 10.21873/invivo.12087
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Results of Surgery for Colorectal Liver Metastases in Terms of Primary Tumour Location and Clinical Risk Factors

Abstract: Background/Aim: The aim of the study was to evaluate the influence of primary tumour location and clinical risk factors for long-term results of surgery for colorectal liver metastases (CLMs). Patients and Methods: Overall survival (OS) and recurrence-free survival (RFS) were evaluated in 636 patients. Patients were divided by tumour location (right-/left-sided colorectal cancer: RCRC/LCRC; rectal cancer), and age, gender, number and size of CLMs, type of liver surgery and interval from primary operation were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…In addition to the many known risk factors affecting the long-term survival of patients with metastatic colon cancer, recent studies have shown that primary tumor location is also an important prognostic factor ( Price et al ., 2015 ; Sasaki et al ., 2016 ; Creasy et al ., 2017 ; Buisman et al , 2020 ; Treska et al ., 2020 ). As a junctional site between the right and left colon, their anatomopathological features have not been fully elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the many known risk factors affecting the long-term survival of patients with metastatic colon cancer, recent studies have shown that primary tumor location is also an important prognostic factor ( Price et al ., 2015 ; Sasaki et al ., 2016 ; Creasy et al ., 2017 ; Buisman et al , 2020 ; Treska et al ., 2020 ). As a junctional site between the right and left colon, their anatomopathological features have not been fully elucidated.…”
Section: Introductionmentioning
confidence: 99%